KESULITAN BELAJAR PADA ANAK:Identifikasi Faktor yang Berperan - M Nur Ghufron (Sekolah Tinggi Agama Islam Negeri (STAIN) Kudus, 2016)
Learning activities for each individual are not always able to take place naturally. This is due to the individual differences among students. Students cannot learn properly called with learning difficulties. Learning difficulties is a drawback that is not outwardly visible. Inability to learn is not to be recognized in a physical form different from people who do not experience problems learning difficulties. This paper identifies factors that contribute the learning affect in children.